Microstructure, mechanical and wear characteristics of CeO2-Mg metal matrix composites. (April 2023) - Anand Babu, V; Kumaravel, A; Manikandan, R
In this study, an attempt is made in producing composite materials by reinforcing cerium oxide with magnesium matrix. Very limited research has been carried out by using cerium oxide as a reinforcement through powder metallurgy technique. Hence the effects of reinforcing cerium oxide on microstructure, mechanical and wear properties in magnesium matrix are studied. The weight percentage of the reinforcement is varied by 3, 6, 9 and 12. Microstructural, mechanical properties like density, microhardness and compression strength and wear properties were studied for the fabricated composites. Scanning electron microscope with energy dispersive X-ray analysis (EDX) and X-ray diffraction (XRD) exhibited uniform distribution of cerium oxide and its presence in the matrix, respectively. Line scan mapping was also carried out on the samples to identify the particles present at that particular region in the matrix. The increase in cerium oxide has reduced the density but increased porosity in the composite materials. The microhardness and compressive strength have gradually increased with an increase of reinforcements. The microhardness has increased up to 40% and compressive strength has increased from 83 to 176 MPa for 12% cerium oxide, respectively. The wear resistance has also increased with an increase in reinforcement and a 28% increase in wear rate was inferred. SEM images of the worn surface exhibited good grain refinement of ceramic oxide in the matrix.